(untitled) (ASEAN Engineering Journal, 2024)
Porang (Amorphophallus oncophyllus) is unable to be consumed directly due to high calcium oxalate content. Two methods commonly used to reduce calcium oxalate contents are a mechanical method by grinding and sieving and in chemical process by using sodium chloride immersion. Most studies focused on how to increase glucomannan content in porang flour. Glucomannan is a hydrocolloid complex sugar used as dietary fiber. It is utilized as a thickening agent, gel-forming agent, and applied in the food and pharmaceutical industries. In previous studies, purification of glucomannan has been done by milling fresh tuber and extraction with multilevel ethanol concentration. In this study, extraction with ethanol 50% and 70% have been done with a variation of extraction time: 15, 30, 45 and 60 minutes. For preparation, porang chips are ground and sieved into 40 mesh flour. After extraction, glucomannan flour was filtered and dried, then characterized. Glucomannan content, calcium oxalate content, moisture content, ash content, viscosity, morphology, Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) analysis were conducted. The experiment results show that the longer duration of extraction significantly decreased calcium oxalate content. Moisture content ranged from 9.99 – 10.85%. Better ash content was obtained at 50% ethanol, which exhibited under 3% of all immersion duration. The morphology of purified glucomannan flour observed through Scanning Electron Microscopy (SEM) showed a small amount of calcium oxalate as indicated by a needle-like structure. Ethanol concentrations and extraction duration effects on the purity and characterization of glucomannan flour from porang chips have been discussed in detail in this study.